Pengaruh Service Excellent dan Fasilitas terhadap Customer Satisfaction Penumpang Kelas Ekonomi - Supriyadi, Agus; Irmadiani, Nadia (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This study aims to determine the effect of Service Excellent and Facilities on Customer Satisfaction (Y) on economy class passengers at Poncol Station PT Kereta Api Indonesia (Persero) DAOP IV Semarang. This research uses descriptive research type. The population in this study consisted of economy class train passengers at Poncol Station which amounted to 919,357 passengers. The sampling technique used in this study was non-probability sampling, with a sample size of 100 respondents. The results of statistical analysis show that Service Excellent has a positive and significant influence on Customer Satisfaction, with a significance value of 0.000 and t count of 8.452, which exceeds the t table value of 1.984. Similarly, the effect of Facilities on Customer Satisfaction is also proven to be significant, with a significance value of 0.000 and a t-statistic of 3.887, which exceeds the t table value of 1.984. The Coefficient of Determination analysis shows that 71.2% of Customer Satisfaction can be explained by Service Excellent and Facilities, while the remaining 28.8% is influenced by other variables. In addition, the F test results show that the Service Excellent and Facility variables simultaneously (together) have a significant influence on Customer Satisfaction, with a calculated f value of 120.040 which exceeds the f table value of 3.09. In conclusion, this study confirms that Service Excellent and Facilities have an important role in increasing Customer Satisfaction on economy class passengers at Poncol Station PT Kereta Api Indonesia (Persero) DAOP IV Semarang. These findings can provide valuable insights for companies in improving service quality and facilities to meet customer expectations and satisfaction. Keywords: service excellent, facility, customer satisfaction